The PARP inhibitor, olaparib, depletes the ovarian reserve in mice: implications for fertility preservation - Winship, Amy L; Griffiths, Meaghan; Lliberos Requesens, Carolina; Sarma, Urooza; Phillips, Kelly-Anne; Hutt, Karla J (Human reproduction (Oxford), 2020)
Abstract STUDY QUESTION What is the impact of the poly(ADP-ribose) polymerase (PARP) inhibitor, olaparib, alone or in combination with chemotherapy on the ovary in mice? SUMMARY ANSWER Olaparib treatment, when administered alone, depletes primordial follicle oocytes, but olaparib does not exacerbate chemotherapy-mediated ovarian follicle loss in mice. WHAT IS KNOWN ALREADY The ovary contains a finite number of oocytes stored within primordial follicles, which give rise to all mature ovulatory oocytes. Unfortunately, they are highly sensitive to exogenous DNA damaging insults, such as cytotoxic cancer treatments. Members of the PARP family of enzymes are central to the repair of single-strand DNA breaks. PARP inhibitors have shown promising clinical efficacy in reducing tumour burden, by blocking DNA repair capacity. Olaparib is a PARP1/2 inhibitor recently FDA-approved for treatment of BRCA1 and BRCA2 mutation carriers with metastatic breast cancer. It is currently being investigated as an adjunct to standard treatment at an earlier stage, potentially curable, BRCA1- and BRCA2-associated breast cancer which affects reproductive age women. Despite this, there is no preclinical or clinical information regarding the potential impacts of olaparib on the ovary or on female fertility. Unfortunately, it may be many years before clinical data on fertility outcomes for women treated with PARP inhibitors becomes available, highlighting the importance of rigorous preclinical research using animal models to establish the potential for new cancer therapies to affect the ovary in humans. We aimed to comprehensively determine the impact of olaparib alone, or following chemotherapy, on the ovary in mice. STUDY DESIGN, SIZE, DURATION On Day 0, mice (n = 5/treatment group) were administered a single intraperitoneal dose of cyclophosphamide (75 mg/kg/body weight), doxorubicin (10 mg/kg), carboplatin (80 mg/kg), paclitaxel (7.5 mg/kg) or vehicle control. From Days 1 to 28, mice were administered subcutaneous olaparib (50 mg/kg) or vehicle control. This regimen is proven to reduce tumour burden in preclinical mouse studies and is also physiologically relevant for women. PARTICIPANTS/MATERIALS, SETTING, METHODS Adult female wild-type C57BL6/J mice at peak fertility (8 weeks) were administered a single intraperitoneal dose of chemotherapy, or vehicle, then either subcutaneous olaparib or vehicle for 28 days. Vaginal smears were performed on each animal for 14 consecutive days from Days 15 to 28 to monitor oestrous cycling. At 24 h after final treatment, ovaries were harvested for follicle enumeration and immunohistochemical analysis of primordial follicle remnants (FOXL2 expressing granulosa cells), DNA damage (γH2AX) and analysis of apoptosis by TUNEL assay. Serum was collected to measure circulating anti-Müllerian hormone (AMH) concentrations by ELISA. MAIN RESULTS AND THE ROLE OF CHANCE Olaparib significantly depleted primordial follicles by 36% compared to the control (P < 0.05) but had no impact on other follicle classes, serum AMH, corpora lutea number (indicative of ovulation) or oestrous cycling. Primordial follicle remnants were rarely detected in control ovaries but were significantly elevated in ovaries from mice treated with olaparib alone (P < 0.05). Similarly, DNA damage denoted by γH2AX foci was completely undetectable in primordial follicles of control animals but was observed in ∼10% of surviving primordial follicle oocytes in mice treated with olaparib alone. These observations suggest that functional PARPs are essential for primordial follicle oocyte maintenance and survival. Olaparib did not exacerbate chemotherapy-mediated follicle depletion in the wild-type mouse ovary. LARGE SCALE DATA N/A. LIMITATIONS, REASONS FOR CAUTION This study was performed in mice, so the findings may not translate to women and further studies utilizing human ovarian tissue and sera samples should be performed in the future. Only one long-term time point was analysed, therefore olaparib-mediated follicle damage should be assessed at more immediate time points in the future to support our mechanistic findings. WIDER IMPLICATIONS OF THE FINDINGS Olaparib dramatically depleted primordial follicles and this could be attributed to loss of intrinsic PARP-mediated DNA repair mechanisms. Importantly, diminished ovarian reserve can result in premature ovarian insufficiency and infertility. Notably, the extent of follicle depletion might be enhanced in BRCA1 and BRCA2 mutation carriers, and this is the subject of current investigations. Together, our data suggest that fertility preservation options should be considered for young women prior to olaparib treatment, and that human studies of this issue should be prioritized. STUDY FUNDING/COMPETING INTEREST(S) This work was made possible through Victorian State Government Operational Infrastructure Support and Australian Government NHMRC IRIISS. This work was supported by funding from the National Health and Medical Research Council (NHMRC); (K.J.H. #1050130) (A.L.W. #1120300). K.A.P. is a National Breast Cancer Foundation Fellow (Australia—PRAC-17-004). K.A.P. is the Breast Cancer Trials (Australia) Study Chair for the OlympiA clinical trial sponsored by AstraZeneca, the manufacturer of olaparib. All other authors declare no competing financial or other interests.